Ứng dụng mô hình định giá tài sản năm yếu tố để giải thích tỉ suất sinh lợi cổ phiếu trên thị trường chứng khoán Việt Nam - Võ Xuân Vinh; Đặng Quốc Thành (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
Capital asset pricing is an important topic in finance. This paper uses the Fama and French’s (2015) five-factor model for explaining stock returns in Vietnam’s stock market. We use a dataset of firms listed on the Ho Chi Minh City Stock Exchange for the period from 2007 to 2014. The results indicate that the market risk premium of CAPM is the best to explain stock returns in the Vietnam’s stock market.